2019
DOI: 10.1007/s42452-019-0751-6
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of slip effects on electroosmotic mixing in heterogeneous microchannels based on entropy index

Abstract: In this article electrokinetic mixing through heterogeneous microchannels has been studied and the effects of slip coefficient, zeta-potential, Debye-Hückel parameter and Reynolds number on mixing efficiency have been investigated. The microchannels studied here, have non-homogenous zeta-potential distribution at the wall, while other surface properties are considered to be homogenous. In order to investigate the electro-osmotic mixing, the Navier-Stokes, Nernst-Planck, Laplace and convection-diffusion equatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…The H–S condition is applied to the boundaries with this simplification, and the velocity field within the flow domain is then solved using this boundary condition. The H–S model’s validity has been well studied for investigating the fluid flow field [ 33 ], and determining concentration field and mixing efficiency has shown that this model can have high accuracy for predicting mixing under suitable conditions and that the maximum error is negligible [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…The H–S condition is applied to the boundaries with this simplification, and the velocity field within the flow domain is then solved using this boundary condition. The H–S model’s validity has been well studied for investigating the fluid flow field [ 33 ], and determining concentration field and mixing efficiency has shown that this model can have high accuracy for predicting mixing under suitable conditions and that the maximum error is negligible [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…The slip presence led to a significant enhancement of energy conversion efficiency in a similar study [ 46 ]. Other studies in this field include the investigation of surface slip phenomenon in the electroosmotic flow of non-Newtonian fluids in porous media [ 47 ], the surface slip examination in microfluidic equipment [ 48 ], the analytical and numerical study of slip flow of Newtonian fluids inside flat microchannels [ 34 , 49 ], and analytical study of electroosmotic slip flow of viscoelastic fluids with pressure gradient in flat [ 50 ] and annular microchannels [ 51 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The most remarkable benefit of the above microfluidic devices, compared to the conventional devices, comes from the unique feature, i.e., the large surface area-to-volume ratio, which significantly improves the mass, heat, and energy transfer rates. This feature can result in not only better proficiency and performance but also greater yield [25,26]. Besides, other positive points such as low reagent consumption, less computational time (time-efficient), low cost (cost-efficient), portability, and high throughput expand their utilization in the domains of microsystems, micro-total analysis systems (µTAS), and lab-on-a-chip (LoC) systems [25,27,28].…”
Section: Introductionmentioning
confidence: 99%